2006
DOI: 10.1093/qjmed/hcl063
|View full text |Cite
|
Sign up to set email alerts
|

A placebo-controlled, double-blind, randomized controlled trial of a natural killer cell stimulant (BioBran MGN-3) in chronic fatigue syndrome

Abstract: The findings do not support a specific therapeutic effect for BioBran in CFS. The improvement showed by both groups over time highlights the importance of placebo controls when evaluating interventions in CFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Twenty of the included trials adopted a two-arm parallel group design [10-12,14,15,17-27,29,30,33,35], three adopted a three-arm parallel group design [16,28,34], and one used a four-arm parallel group design [13], while two trials employed a cross-over design [31,32]. Nine trials adopted the CDC criteria for the diagnosis of CFS [11,20,22,24,25,27,28,31,32], five studies diagnosed CFS according to the criteria published by Fukuda [10,15,16,19,21], five used the Oxford criteria [12,17,18,30,35], two combined with Fukuda and Oxford criteria [13,23], and one used a different classification system [33]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty of the included trials adopted a two-arm parallel group design [10-12,14,15,17-27,29,30,33,35], three adopted a three-arm parallel group design [16,28,34], and one used a four-arm parallel group design [13], while two trials employed a cross-over design [31,32]. Nine trials adopted the CDC criteria for the diagnosis of CFS [11,20,22,24,25,27,28,31,32], five studies diagnosed CFS according to the criteria published by Fukuda [10,15,16,19,21], five used the Oxford criteria [12,17,18,30,35], two combined with Fukuda and Oxford criteria [13,23], and one used a different classification system [33]. …”
Section: Resultsmentioning
confidence: 99%
“…Eleven RCTs had an adequate method for random sequence generation [10,11,13,15,17,19,24,25,28,29,33], whereas the remaining 15 RCTs did not [12,14,16,18,20-23,26,27,30-32,34,35]. Allocation concealments were adequately performed in 13 RCTs [10,11,13,17,19,24,25,29-33]. Patient and assessor blinding was reported in 16 of the RCTs [17-20,22-27,29-34], whereas two RCTs employed assessor blinding only [10,11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most likely reason for these discrepancies is that the present study examined healthy subjects, whereas the previous studies all examined the effects of RBEP in the context of cancer. McDermott et al [17] concluded that arabinoxylan supplementation was not effective for treating chronic fatigue syndrome, an assessment thought to indirectly measure NK cell activity. Cancer patients have been suggested to have reduced NK cell activity compared with healthy individuals [18,19]; thus, significant effects on NK cell activity in healthy individuals may be difficult to observe.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the best evidence based and standardized immunodulators without any side effects are plant extracts and they are all over the world registered only as food supplements. There are growing evidences that plant PAMP-like molecules (such as standardized rice bran arabinoxylan concentrate) exhibit a lot of immunological [15][16][17][18][19][20][21][22][23][24][25][26] and clinical benefit [27][28][29]. Therefore, further clinical trials are necessary to investigate this beneficial interaction.…”
Section: Discussionmentioning
confidence: 99%